Strategy for Building Optimal Performance of Medical Laboratory Technologists: Synergy of Organizational Culture and Work Environment with Job Satisfaction as an Intervening Variable - Gumelar, Angga; Nuraeni, Nuraeni (Dinasti Publisher, 2025)
This research aims to find out the determinants of job satisfaction and its impact on the performance of ATLM Hospital employees in West Java Province (Bekasi, Sukabumi, Karawang). The research method used in this research is a quantitative method with an associative approach. The number of research respondents used was 120 hospital employees, namely Medical Laboratory Technologists (ATLM) in West Java Province (Bekasi, Sukabumi, Karawang), while the sampling technique was probability sampling with stratified sampling with a methodical approach used to ensure that each subgroup (strata) in the population is well represented in the sample. The results of the research are (a) organizational culture has no and no significant effect on ATLM job satisfaction, (b) organizational culture has a positive and significant effect on employee performance, (c) job satisfaction has a positive and significant effect on employee performance, (d) the work environment has an effect positive and significant on employee job satisfaction, (e) the work environment has a positive and significant effect on employee performance, (f) organizational culture has no and no significant effect on employee performance through job satisfaction, and (g) the work environment has a positive and significant effect on performance employees through job satisfaction.